KEMANDIRIAN DAN KEMAMPUAN KEUANGAN DAERAH DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI RIAU - Sri Maryanti; Hefrizal Handra; Efa Yonnedi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
The study aims to analyze regional financial independence, regional financial capabilities, and their impact on economic growth in Riau province. To analyze it, it uses the calculation of the ratio of financial independence and the ratio of regional financial capabilities and uses the degree of fiscal decentralization, while the economic growth rate uses the PDRB of Riau province. Data was used in 2017-2022 with data processing using the Stata 15 application. From the analysis, the level of financial independence in Riau province for 2017-2019 is very low with an instructive relationship pattern, meaning that the central government is dominant in financial independence when compared to the role of the Riau provincial government itself. In 2020-2022, the ratio of financial independence of the Riau province is low with a pattern of constructive relations, meaning that the role of the central government is slightly reduced and the role of the central government, in this case, is only a consulting provider related to the implementation of regional autonomy in the Riau region. The ratio of regional financial capabilities in Riau province is still in the sufficient category for 2017-2018 and 2021-2022 and the category is less for 2019-2020, meaning that the role of the central government is still needed but not as large as the previous year. Partially only the financial capabilities of the regions affect economic growth but simultaneously both free variables have no effect. This means that the higher the regional financial capability, the more economic growth in Riau. If regional financial independence is higher, it will not have an impact on increasing economic growth in Riau.